Multi-person Decision Model for Unfinished Construction Project - Utomo, Christiono (IPTEK The Journal for Technology and Science, 2010)
This paper discusses a proposed model of multi-person decision on prioritizing selection with regard to continuing or terminating unfinished construction projects. This involved multiple steps including determining criteria and sub criteria, selecting and weighting of alternatives, optimizing, and analyzing coalition formation and agreement option. Criteria and sub criteria that were obtained from perspectives of 120 project managers are the first basis to construct decision hierarchy. The model is implemented in one of the biggest private construction projects in Indonesia. The implementation was based on the Analytic Hierarchy Process for multi criteria decision involving coalition and agreement options in a multi-person decision. Goal Programming was used to optimize based on cost constrains. The results demonstrate a process of multiperson decision to select priorities of each alternative to each decision and concluded that some of the projects were continued, postponed or terminated. The new direction of research presented in this paper presents some interesting challenges to those involved in modeling computer-based multi-person decision support utilizing both Multi Agent System and Multi Criteria Decision Making.